Centella asiatica Extract Attenuates Kidney Fibrosis Through Reducing Mesenchymal Transition and Inflammation in Ureteral Ligation Model in Mice - Sari, Dwi Cahyani Ratna; Budiharjo, Santosa; Afifah, Husnari; Jasmin, Destantry; Kokasih, Orisativa; Putri, Tiara Gitami; Arifiani, Karina; Setyaningsih, Wiwit Ananda Wahyu; Arfian, Nur (Frontiers in Pharmacology, 2021)
Background: Kidney fibrosis is the common final pathway of chronic kidney disease (CKD), and is characterized by inflammation, mesenchymal transition with myofibroblast formation and epithelial to mesenchymal transition (EMT). Centella asiatia (CeA) is an herb that has a reno-protective effect. However, its mechanism of action in kidney fibrosis has not been elucidated. Aim: To elucidate the effect of CeA in amelioration of kidney fibrosis in a unilateral ureteral obstruction (UUO) model and focus on mesenchymal transition and inflammation. Methods: Unilateral ureteral obstruction was performed in male Swiss-background mice (age: 2–3 mon, weight: 30–40 g, UUO group n=6) to induce kidney fibrosis. Two doses of CeA extract with oral administration, 210 and 840 mg/Kg body weight were added in UUO (U+C210 and U+C840 groups, each n=6). The sham operation procedure was performed for the control group (SO, n = 6). The mice were euthanized at day-14 after operation. Tubular injury and interstitial fibrosis area fractions in kidney tissues of the mice were quantified based on periodic acid-Schiff (PAS) and Sirius Red (SR) staining. Immunostaining was performed for examination of fibroblast (PDGFR-β), myofibroblast (α-SMA), Monocyte Chemoattractant Protein-1 (MCP-1) and macrophage (CD68), meanwhile double immunofluorescence was performed with PDGFR-β and α-SMA. Reverse transcriptase-polymerase chain reaction (RT-PCR) was performed to examine mRNA expression of TGF-β, Collagen-1, Snail, E-cadherin, vimentin, fibroblast-specific protein 1 (FSP-1), CD68, toll-like receptor 4 (TLR4), and MCP-1. Results: We observed a significantly higher interstitial fibrosis area fraction and tubular injury (p<0.001) with fibroblast expansion and myofibroblast formation in the UUO group than in the SO group. These findings were associated with higher mRNA expression of TGF-β, Collagen-1, Snail, vimentin, FSP-1, CD68, TLR4, and MCP-1 and lower mRNA expression of E-cadherin. The U+C840 group had a significantly lower tubular injury score and interstitial fibrosis area fraction, which associated with downregulation of mRNA expression of TGF-β, Collagen-1, Snail, vimentin, FSP-1, CD68, TLR4, and MCP-1, with upregulation of mRNA expression of E-cadherin. Immunostaining observation revealed the U+C840 group demonstrated reduction of macrophage infiltration and myofibroblast expansion. Conclusion: CeA treatment with dose-dependently ameliorates mesenchymal transition and inflammation in kidney fibrosis in mice.